2017
DOI: 10.1159/000484525
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Genetic Perspective of Eating Disorders

Abstract: Eating disorders (ED) including anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED) affect up to 5% of the population in Western countries. Risk factors for developing an ED include personality traits, family environment, gender, age, ethnicity, and culture. Despite being moderately to highly heritable with estimates ranging from 28 to 83%, no genetic risk factors have been conclusively identified. Our objective was to explore evolutionary theories of EDs to provide a new perspective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 148 publications
(202 reference statements)
0
25
0
4
Order By: Relevance
“…Although the genetic study of BED is still in early stages and there are no enough genome-wide association studies (GWAS) focused exclusively on BED, preliminary evidences suggests that could there be predisposing risk factors [ 171 , 172 , 173 , 174 ]. In fact, there are good evidences that heritable factors make a significant contribution to the risk of developing eating disorders [ 175 ]. Patrono et al showed that exposure to environmental conditions induces compulsion-like eating behaviour, depending on genetic background.…”
Section: Binge Eating Disorder a “Full-fledged” Pathologymentioning
confidence: 99%
“…Although the genetic study of BED is still in early stages and there are no enough genome-wide association studies (GWAS) focused exclusively on BED, preliminary evidences suggests that could there be predisposing risk factors [ 171 , 172 , 173 , 174 ]. In fact, there are good evidences that heritable factors make a significant contribution to the risk of developing eating disorders [ 175 ]. Patrono et al showed that exposure to environmental conditions induces compulsion-like eating behaviour, depending on genetic background.…”
Section: Binge Eating Disorder a “Full-fledged” Pathologymentioning
confidence: 99%
“…Multiple genes responsible for monogenic syndromic and non‐syndromic, oligogenic and polygenic forms of obesity have been identified . However, it is unclear as to which genes may predispose individuals to BED . Genetic variants and mutations in and near the melanocortin 4 receptor gene ( MC4R ) locus are linked with polygenic forms of leanness and monogenic, oligogenic and polygenic forms of obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Both BED and obesity have strong genetic underpinnings (9)(10)(11). Heritability estimates for BED and obesity range from 41% to 57% and from 25% to 90% (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, considerable progress has been made to understand the neurobiological mechanisms that underlie ED, converging that genetic factors and gene/environment interactions could contribute to the potential development of these disorders [ 186 , 187 , 188 , 189 ]. One of the possible candidates that may contribute to the dysregulation of feeding patterns in ED and risk of weight gain, leading to obesity, is the polymorphism of DRD4 gene.…”
Section: Drd4 and Feeding Behaviormentioning
confidence: 99%